2014
DOI: 10.1002/pola.27113
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in semipermeable membrane performance of wholly aromatic polyamide through an additive processing strategy

Abstract: A new concept for the method to provide semipermeability in ultrathin and single-component wholly aromatic polyamide membranes has been developed for the first time. It was found that water molecules could permeate through the membrane prepared not from polyamides containing flexible ether, bulky binaphthyl, or fluorene rigid units, but one with carboxylic acid groups under a reverse osmosis mode. However, the enhancement of water transport properties by introducing the hydrophilic group of polyamide was not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Despite the introduction of the N ‐methyl amide linkage, the water permeation cannot be observed for PA‐0‐20 . These results agree with our previous report, which revealed that the ultrathin semipermeable membrane based on PAs without a carboxylic acid group could not show any water permeation even if a flexible or rigid molecular unit was incorporated into the polymer backbone . On the other hand, PA‐20‐0 , PA‐20‐20 , PA‐20‐40 , and PA‐20‐60 with a carboxylic acid group show a water permeation property.…”
Section: Resultssupporting
confidence: 92%
“…Despite the introduction of the N ‐methyl amide linkage, the water permeation cannot be observed for PA‐0‐20 . These results agree with our previous report, which revealed that the ultrathin semipermeable membrane based on PAs without a carboxylic acid group could not show any water permeation even if a flexible or rigid molecular unit was incorporated into the polymer backbone . On the other hand, PA‐20‐0 , PA‐20‐20 , PA‐20‐40 , and PA‐20‐60 with a carboxylic acid group show a water permeation property.…”
Section: Resultssupporting
confidence: 92%
“…In our previous study, we reported that the introduction of the N ‐methyl amide linkage suppressed the hydrogen bonding, conformational changes, and inter‐/intramolecular interactions among the polymers, implying that there would be differences in the internal structure of these membranes . In fact, the decrease in the dry density of the polymer was confirmed after the N ‐methylation (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…N ‐Methylpyrrolidone (NMP) was purchased from Wako Pure Chemical Industries. Partially N ‐methylated random aromatic polyamides were prepared according to a previous report …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 However, in the case of PBI ultrathin membrane, it is obvious that water permeation phenomenon was confirmed without introducing the hydrophilic groups into the polymer backbones (Table II). This result is probably due to the nature of the imidazole ring, which makes PBI molecules self-charged in aqueous environment, resulting in the assistance for the formation of water transporting channels.…”
Section: Synthesis Of Various Polybenzimidazolesmentioning
confidence: 95%